Kebijakan Tentang Kurikulum Pendidikan Agama Islam Pada Era Reformasi; Penerapannya Pada Sekolah Non Islam di Purworejo - Fadhlurrahman (SALIHA: Jurnal Pendidikan & Agama Islam, 2020)
This article examines the Government's Policy on the Islamic Religious Education Curriculum in the Reformation Era, followed by a case study on the application of Islamic Religious Education to Non-Islamic Schools in Purworejo. The author tries to present the study of Islamic Education in the third millennial, the renewal of Islamic education in Indonesia, the era of regional autonomy, problems in the Islamic education system, the curriculum system in the reform era to the case studies in Purworejo. The author uses descriptive analysis method to explain the curriculum of Islamic religious education in the reform era. As for the case study, researchers collected data by interview and then analyzed qualitative data so that accurate data was seen from research sources. Researchers found a picture of the Islamic Religious Education curriculum in the Reformation Era from 1964 to 2013. Strengthened by the application of Islamic Religious Education in non-Islamic schools in Purworejo, which was not yet fully maximized as mandated by PP 55 of 2007. So that it gave rise to ideas and ideas so that their application was in accordance with the rules applicable.